2019
DOI: 10.1001/jamafacial.2018.0999
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescription Patterns After Rhinoplasty

Abstract: Results | We included 158 464 041 combined views, with a mean of 660 267 views per video. The mean age of the videos was 4 years (range, 9 days to 11 years) and the mean length was 10.18 minutes (range, 0.50-51.18 minutes). The term nose job received the most views, totaling 56 251 991 views with a mean of 2 812 600 views per video. The mean DISCERN rating was 2.21 overall, and blepharoplasty had the highest mean rating of 2.75. The DISCERN rating for bias was 2.78 (Table 2). The correlation coefficient for vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
4
17
0
Order By: Relevance
“…Nevertheless, there is much to gain by looking at the similarities and differences in those studies. Similar to other recent studies, our patients who underwent ESS had increased opioid consumption when a concurrent septoplasty and/or turbinoplasty was performed, and, comparable to work by Riley et al and Raikundalia et al, the extent of ESS (full vs limited) did not significantly influence pain control or opioid use . Although there are mixed results on the influence of age on opioid usage, our results are similar to others showing that younger patients require slightly more .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, there is much to gain by looking at the similarities and differences in those studies. Similar to other recent studies, our patients who underwent ESS had increased opioid consumption when a concurrent septoplasty and/or turbinoplasty was performed, and, comparable to work by Riley et al and Raikundalia et al, the extent of ESS (full vs limited) did not significantly influence pain control or opioid use . Although there are mixed results on the influence of age on opioid usage, our results are similar to others showing that younger patients require slightly more .…”
Section: Discussionsupporting
confidence: 91%
“…Similar to other recent studies, our patients who underwent ESS had increased opioid consumption when a concurrent septoplasty and/or turbinoplasty was performed, and, comparable to work by Riley et al and Raikundalia et al, the extent of ESS (full vs limited) did not significantly influence pain control or opioid use. 12,[22][23][24] Although there are mixed results on the influence of age on opioid usage, our results are similar to others showing that younger patients require slightly more. 12,22,23 However, as in our study with a very mild negative correlation with increasing age and other studies showing no correlation between age and opioid use, the clinical significance of this is not likely drastic.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[6][7][8] A previous study has demonstrated that when surgeons perceive opioid abuse to be a big/moderate problem among their patients, a subsequent reduction in opioid prescription ensues. 9 While opioid prescription patterns among facial plastic surgeons after rhinoplasty have been previously reported, [2][3][4] no research has evaluated the perceptions of facial plastic surgeons on opioid dependence in the rhinoplasty population.…”
mentioning
confidence: 99%